Acquired Hemophilia A (FVIII Deficiency) Associated with Papillary Thyroid Cancer: Treatment with Recombinant Porcine FVIII. (28th August 2019) - Nguyen, S.; Teh, P.; Zhou, J.; Chang, E. Y.; von Drygalski, A.
Abstract : Acquired hemophilia A (AHA) is a rare autoimmune disorder caused by autoantibodies against Factor VIII (FVIII). It has a high mortality due to bleeding complications. FVIIa-based bypassing agents are the first line of treatment but not always effective. Recombinant porcine (rp) FVIII (Obizur®) was recently approved for rescue treatment but with little evidence-based information regarding efficacy. We report a case of papillary thyroid cancer associated with AHA malignancy that responded to a single dose of rpFVIII after failure to achieve hemostasis with FVIIa-based bypassing products.